Porous Silicon 1994
DOI: 10.1142/9789812812995_0009
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Technique Study of Porous Silicon Membranes by Raman Scattering, Ftir, Xps, Aes and Sims

Abstract: Optical and surface analytical techniques of Raman scattering, Fourier transform infrared (FTIR) spectroscopy, x-ray photoelectron spectroscopy, Auger electron spectroscopy and secondary ion mass spectrometry have been used to study porous Si membranes with visible light emission. The Raman features from porous Si membranes are markedly distinct from that of crystalline, microcrystalline and amorphous Si. Their anomalous Raman-temperature behavior is explained by the quantum wire model and strain effects. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These peaks are similar to previous XPS analysis of PS. 29 Feng et al has shown that 200 mm thick PS membranes showed similar peak positions to those observed here for the PS and Si particles. 29 Quantification of elements from XPS analysis is given in Table 2 with relative percentage concentrations of F at 2%, C at 28.6%, Si at 60.2%, and O at 9.2% for 2E-100.…”
Section: Diffraction Contrast Imaging Of Porous Silcion Nanosponge Pa...supporting
confidence: 86%
See 4 more Smart Citations
“…These peaks are similar to previous XPS analysis of PS. 29 Feng et al has shown that 200 mm thick PS membranes showed similar peak positions to those observed here for the PS and Si particles. 29 Quantification of elements from XPS analysis is given in Table 2 with relative percentage concentrations of F at 2%, C at 28.6%, Si at 60.2%, and O at 9.2% for 2E-100.…”
Section: Diffraction Contrast Imaging Of Porous Silcion Nanosponge Pa...supporting
confidence: 86%
“…9. The features between 900-1000 cm 21 indicate second order optical modes, 29 as seen in both samples 2E-100 and 2E-60. It has also been shown that surface strain or stress in PS can also contribute to a downshift in the Raman peak as is observed from 2E-bulk Si to 2E-100 in Fig.…”
mentioning
confidence: 73%
See 3 more Smart Citations